2022
DOI: 10.1200/cci.21.00170
|View full text |Cite
|
Sign up to set email alerts
|

Using Adversarial Images to Assess the Robustness of Deep Learning Models Trained on Diagnostic Images in Oncology

Abstract: PURPOSE Deep learning (DL) models have rapidly become a popular and cost-effective tool for image classification within oncology. A major limitation of DL models is their vulnerability to adversarial images, manipulated input images designed to cause misclassifications by DL models. The purpose of the study is to investigate the robustness of DL models trained on diagnostic images using adversarial images and explore the utility of an iterative adversarial training approach to improve the robustness of DL mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Comparing the VGG16 and ResNet50 CNN models, the VGG16 performed better on the present dataset and hyperparameters. The VGG16 is a CNN architecture that has been demonstrated to improve robustness depending on the environment of the model 13 , and this was also observed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Comparing the VGG16 and ResNet50 CNN models, the VGG16 performed better on the present dataset and hyperparameters. The VGG16 is a CNN architecture that has been demonstrated to improve robustness depending on the environment of the model 13 , and this was also observed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…1,[3][4][5][6] Manual segmentation is timeconsuming and is prone to intra-and inter-observer variability. 7,8 With the advent of deep learning to automate various image analysis tasks, 9,10 there has been increasing enthusiasm to use deep learning for brain image autosegmentation. [11][12][13][14] UNets are among the most popular and successful deep learning auto-segmentation algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…VGG16 has a structure in which the "convolution layer/convolution layer/pooling layer" is repeated twice, and the "convolution layer/convolution layer/convolution layer/pooling layer" is repeated three times, followed by three fully connected layers. It was reported that VGG16 is a model that can be expected to further improve robustness in recent year 28 . Therefore, we selected VGG16 as the CNN model in this study.…”
Section: Methodsmentioning
confidence: 99%